2019
DOI: 10.1038/s41598-019-41947-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of autophagy on the survival and invasive activity of Eimeria tenella sporozoites

Abstract: Autophagy is a cellular process that is vital for the maintenance of homeostasis in eukaryotic cells. Currently, autophagy-related genes ( atgs ) in the Eimeria tenella genome database have been reported, but very little is known about the effects of autophagy on the survival and invasive activity of this protozoan. In this study, we investigated the autophagy in E. tenella sporozoites under starvation and autophagy-modulators treatments and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…ATG8 in E. tenella sporozoites activates upon starvation [90]. Deletion of another autophagy protein in T. gondii (ATG3) inhibits conjugation of ATG8 to the autophagosome, thereby disrupting mitochondrial homeostasis and normal growth of tachyzoites [91].…”
Section: Plos Onementioning
confidence: 99%
“…ATG8 in E. tenella sporozoites activates upon starvation [90]. Deletion of another autophagy protein in T. gondii (ATG3) inhibits conjugation of ATG8 to the autophagosome, thereby disrupting mitochondrial homeostasis and normal growth of tachyzoites [91].…”
Section: Plos Onementioning
confidence: 99%
“…Qi Nanshan et al also proved that starvation and the autophagy inducer rapamycin ( RAPA ) could induce autophagy in E. tenella sporozoites, while 3-Methyladenine ( 3-MA ) could inhibit sporozoite autophagy. RAPA induced sporozoite autophagy could enhance sporozoite invasion into chick embryo fibroblasts, while 3-MA inhibited sporozoite autophagy and reduced sporozoite invasion ( Qi et al, 2019 ). Zhang (2020b) found that the expression of Beclin-1 mRNA and LC3-II protein was significantly increased after E. tenella infection of chick embryo cecal epithelial cells .…”
Section: Introductionmentioning
confidence: 99%